2021
DOI: 10.1002/jcp.30283
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide and mesenchymal stem cells‐extracted microvesicles attenuate LPS‐induced Alzheimer's disease

Abstract: Both hydrogen sulfide (H2S) and mesenchymal stem cells (MSCs) extracted microvesicles (MVs) are potent anti‐inflammatory molecules. They play an essential role in lowering the production of tumor necrosis factor‐alpha (TNF‐α). The latter could strongly stimulate MiR‐155 that contributes to neurodegeneration and Alzheimer's disease (AD). miR‐155 could repress the expression of inositol 5‐phosphatase‐1 (SHIP‐1) leading eventually to activation of Akt kinase and neurofibrillary development in AD. The current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The action of other anti-inflammatory molecules on miR-155 expression has been investigated, such as hydrogen sulfide (H 2 S) and microvesicles extracted from mesenchymal stem cells (MSC). AD was induced in albino Wistar rats by intraperitoneal injection of LPS; monotherapy treatment reduced miR-155 levels and inflammation, decreased apoptosis and improved histopathological alterations of the hippocampus [ 65 ].…”
Section: Mir-155mentioning
confidence: 99%
“…The action of other anti-inflammatory molecules on miR-155 expression has been investigated, such as hydrogen sulfide (H 2 S) and microvesicles extracted from mesenchymal stem cells (MSC). AD was induced in albino Wistar rats by intraperitoneal injection of LPS; monotherapy treatment reduced miR-155 levels and inflammation, decreased apoptosis and improved histopathological alterations of the hippocampus [ 65 ].…”
Section: Mir-155mentioning
confidence: 99%
“…Proteins from brain tissues were extracted using a protein extraction kit. Proteins were extracted by using lysis buffer (radioimmunoprecipitation assay (RIPA) buffer with protease and phosphatase inhibitor) on ice for 30 min in a shaker as it was previously done in Aboulhoda et al, (2021), After centrifugation of the tissues at 16,000 g for 30 min at 4℃, the debris was removed. Then, the supernatants were transferred to other tubes for concentration determination and protein analysis.…”
Section: Mmp-9 Protein and Wnt/β-catenin Levels Using Western Blot Techniquementioning
confidence: 99%
“…For example, Adriane D et al [6] used a high-throughput microarray platform and microarray technology to study the expression changes of mi­RNAs in patients with AD, and 6 miRNAs were identified to be aberrantly expressed in the temporal gyrus of patients. Also, in the basic experimental study, similar changes of miRNAs have been observed in AD mice or cell models, such as miR-331-3p and miR-155 [7, 8]. miR-381-3p is a tumor suppressor molecule that plays an important role in a variety of tumors [9, 10].…”
Section: Introductionmentioning
confidence: 88%